2012
DOI: 10.1172/jci61034
|View full text |Cite
|
Sign up to set email alerts
|

Imiquimod clears tumors in mice independent of adaptive immunity by converting pDCs into tumor-killing effector cells

Abstract: Imiquimod is a synthetic compound with antitumor properties; a 5% cream formulation is successfully used to treat skin tumors. The antitumor effect of imiquimod is multifactorial, although its ability to modulate immune responses by triggering TLR7/8 is thought to be key.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
255
3
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 260 publications
(284 citation statements)
references
References 50 publications
13
255
3
3
Order By: Relevance
“…Keratinocyte cell death was reduced in the presence of pan-caspase or caspase-1 inhibitors (Fig. 4c), which provides an explanation for the recently reported TLR7-independent death of keratinocytes 7 . Caspase-1-dependent lysis of keratinocytes is called 'pyroptosis', a mechanism that is distinct from apoptosis and independent of apoptosis-related caspases 41 .…”
Section: Article Nature Communications | Doi: 101038/ncomms2566supporting
confidence: 70%
See 4 more Smart Citations
“…Keratinocyte cell death was reduced in the presence of pan-caspase or caspase-1 inhibitors (Fig. 4c), which provides an explanation for the recently reported TLR7-independent death of keratinocytes 7 . Caspase-1-dependent lysis of keratinocytes is called 'pyroptosis', a mechanism that is distinct from apoptosis and independent of apoptosis-related caspases 41 .…”
Section: Article Nature Communications | Doi: 101038/ncomms2566supporting
confidence: 70%
“…4d), suggesting that Aldara activates the NLRP1 inflammasome. It was recently shown that IMQ itself induces apoptosis in a TLR7-independent fashion 7,19 , but there is no evidence that the Aldara vehicle can act on keratinocytes directly. We thus investigated whether IMQ or another component in the Aldara vehicle cream mediates inflammasome activation.…”
Section: Article Nature Communications | Doi: 101038/ncomms2566mentioning
confidence: 99%
See 3 more Smart Citations